Artificial Intelligence in Education: Readiness, Perceptions, and Implementation in an Early Childhood Teacher Education Program at Universitas Mataram - Fahruddin; Mansur Hakim; Hasanuddin Chaer; Lale Dewi Nurlita Safitri (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2026)
Background: Early Childhood Teacher Education Program (PGPAUD) requires complex pedagogical translation of content into concrete learning experiences. In this context, Artificial Intelligence (AI) has the potential to support prospective teachers in developing personalized learning media, generating age-appropriate instructional content, and simulating interactive environments aligned with children’s cognitive and socio-emotional development.Objective: This study aims to examine the readiness, perceptions, and implementation of AI in learning activities within the PGPAUD program, Faculty of Teacher Training and Education, Universitas Mataram.Method: This research employed a descriptive qualitative approach. The participants consisted of lecturers and students of the PGPAUD program. Data were collected through interviews, observations, and documentation using relevant research instruments. The data were analyzed using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing.Results: The findings indicate that lecturers and students demonstrate adequate digital readiness. However, the integration of AI in instructional practices remains limited. While AI improves learning efficiency and access to information, its use remains largely individual and exploratory due to limited training, lack of experience, and a absence of institutional policies.Conclusion: Integrating AI into PGPAUD requires institutional support, targeted training, and clear policy frameworks. This study helps Indonesian higher education design adaptive, AI-integrated curricula, particularly for teacher education.